Selection Indices Studies in Maize (Zea mays L.) under Multiple Abiotic Stress Conditions - Massey, Preeti; Verma, S. S.; Warsi, M. Z. K. (International Journal of Bio-resource and Stress Management, 2023)
The present investigation was undertaken on maize (Zea mays L.) under two abiotic stress conditions viz. low-nitrogen (low soil fertility) and excess soil moisture conditions (waterlogging) during kharif 2010. Studies were carried out for developing suitable selection indices in relation to multiple abiotic stress tolerance. The experimental material consisted of twelve lines and four testers and their 48 single crosses planted in Randomized Block Design. Analysis of variance revealed significance for all the traits studied in both the conditions, indicating there by the existence of high genetic variability in the genotypes. In low-N conditions, the best performing line was L5 followed by and among testers T3 ranked highest. Among the crosses, L11×T4 ranked highest followed by L8×T1 and L11×T3. In waterlogging conditions, L6 performed better followed by L5. Among the crosses L6×T4 ranked highest. Economic weights were assigned to various traits under low-nitrogen and excess soil moisture (ESM) conditions. Among the crosses, aggregate score were higher in most of the cases but general trend was that ESM traits had the lower score values. Crosses L11×T4, L8×T1, L11×T3, L7×T2 and L6×T2 performed well in low-nitrogen conditions for the assigned selection criteria. In waterlogging trials, L6×T4, L7×T2 and L4×T1 performed excellent while crosses L5×T1, L12×T2, L5×T4, and L3×T3 ranked very low in ESM trials. Thus for ESM tolerance, the crosses L6×T4 and L7×T2 are the best available crosses according to the given selection criteria and for low-nitrogen tolerance, L11×T4 and L8×T1 were the best crosses.